2023
DOI: 10.1108/ijaim-09-2022-0203
|View full text |Cite
|
Sign up to set email alerts
|

IFRS 9 and earnings management: the case of European commercial banks

Abstract: Purpose This paper examines the impact of International Financial Reporting Standards (IFRS) 9 on earnings management (EM) using data from 2011 to 2019 of 100 commercial banks in Europe. Design/methodology/approach Using data from 2011 to 2019 of 100 commercial banks in Europe, the authors conducted several empirical investigations to test the mediating role of IFRS 9 on earnings manipulation through loan loss provision (LLP) by banks. Findings The result shows that the new accounting standards (IFRS 9) si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…This statistically more significant relevance in the previous ICL model, regarding the management of earnings and equity by Portuguese banks in the recognition of LLP, aligns with studies reporting delays in recognizing LLP in the ICL model of IAS 39 and even hiding inevitable losses (Gebhard & Novotny-Farkas, 2011;Hoogervorst, 2014). The unified European regulation, through the EBA, may have minimized the impact of LLP recognition on earnings management in the ECL model compared to ICL (Nnadi et al, 2023), thereby demonstrating that regulation is important in minimizing the possibility of earnings management, providing discipline and transparency to the market (Onali et al, 2021).…”
Section: Analysis and Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This statistically more significant relevance in the previous ICL model, regarding the management of earnings and equity by Portuguese banks in the recognition of LLP, aligns with studies reporting delays in recognizing LLP in the ICL model of IAS 39 and even hiding inevitable losses (Gebhard & Novotny-Farkas, 2011;Hoogervorst, 2014). The unified European regulation, through the EBA, may have minimized the impact of LLP recognition on earnings management in the ECL model compared to ICL (Nnadi et al, 2023), thereby demonstrating that regulation is important in minimizing the possibility of earnings management, providing discipline and transparency to the market (Onali et al, 2021).…”
Section: Analysis and Discussion Of Resultsmentioning
confidence: 99%
“…As previously mentioned, Onali et al (2021) suggest that the ECL model could lead to greater banking transparency and more effective market discipline. A recent study by Nnadi et al (2023) found an increase in earnings management among banks outside the EU following the introduction of IFRS 9, with no evidence of any difference in earnings management behavior for banks within the EU. Conversely, Norouzpour et al (2023) observed a general increase in earnings and equity management following the adoption of IFRS 9, highlighting that this increase was observed in banks located in countries with low regulation.…”
Section: Analysis Of the Ifrs 9 Ecl Modelmentioning
confidence: 92%
“…This more statistically significant relevance in the previous ICL model, regarding the management of earnings and equity by Portuguese banks in the recognition of LLP, aligns with studies reporting delays in recognizing LLP in the ICL model of IAS 39 and even hiding inevitable losses (Gebhardt and Novotny-Farkas 2011;Hoogervorst 2014). The unified European regulation, through the EBA, may have minimized the impact of LLP recognition on earnings management in the ECL model compared to ICL (Nnadi et al 2023), thereby demonstrating that regulation is important in minimizing the possibility of earnings management, providing discipline and transparency to the market (Onali et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, standard-setters' concerns might not be safeguarded, as the dynamic provisions present in this new model can potentially promote earnings management, impairing the transparency of financial statements (FASB-IASB 2009). Studies have shown mixed results regarding the impact of IFRS 9 on earnings management, with some indicating an increase in such practices, especially in less regulated environments (Nnadi et al 2023;Norouzpour et al 2023).…”
Section: Impact Of Dynamic Models On Economic Cycles Managementmentioning
confidence: 99%